Prognostic Significance of Neutrophil-to-Lymphocyte Ratio in Colorectal Liver Metastasis: A Systematic Review and Meta-Analysis. - Haowen Tang; Bingmin Li; Aiqun Zhang; Wenping Lu; Canhong Xiang; Jiahong Dong (PLoS ONE, 2016)
Background and objective Inflammation is deemed to play critical roles in tumor progression and metastasis, and an increased neutrophil-lymphocyte ratio (NLR) has been reported to correlate with poor survivals in various malignancies. However, association between NLR elevation and survival outcome in patients with colorectal liver metastasis (CRLM) remains controversial. The aim of this study was to investigate the prognostic significance of elevated NLR in CRLM. Methods The meta-analysis was conducted in adherence to the MOOSE guidelines. PubMed, Embase, Cochrane Library, Web of Science and the Chinese SinoMed were systematically searched to identify eligible studies from the initiation of the databases to May, 2016. Overall survival (OS) and recurrence free survival (RFS) were pooled by using hazard ratio (HR) with corresponding 95% confidence interval (CI). Correlation between NLR values and clinicopathological features was synthesized by using odds ratio (OR) with corresponding 95% CI. Results A total of 1685 patients from 8 studies (9 cohorts) were analyzed, consisting 347 (20.59%) in high pretreatment NLR value group and 1338 (79.41%) in low pretreatment NLR value one. The results demonstrated that elevated pretreatment NLR was significantly related to poor OS (HR 2.17, 95% CI 1.82-2.58) and RFS (HR 1.96, 95% CI 1.64-2.35) in patients with CRLM. Conclusion The result of this systematic review and meta-analysis indicated that an elevated pretreatment NLR was closely correlated with poor long-term survival (OS and RFS) in CRLM patients. NLR can be routinely monitored and serve as a useful and cost-effective marker with strong prognostic significance in patients with CRLM.